The Gambler’s Fallacy, the Halo Effect, and the Familiarity Effect Based on Risk Profile: Bullish and Bearish Market in Indonesia Stock Exchange - Putu Anom Mahadwartha; Fitri Ismiyanti; Zunairoh Zunairoh (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
This study tests three behavioral biases: the gambler’s fallacy, the halo effect, and the familiarity effect. The novelty is the behavioral bias in bullish and bearish markets, based on different investors’ risk profiles. The questionnaire used a Likert scale. This study argues that bullish and bearish markets, and different risk profiles, affect investors’ behavioral bias. The gambler’s fallacy occurs when markets are bullish and partially when markets are bearish. The halo effect without risk profile does not occur in either market, and the familiarity effect occurs in both markets. Investors with a very conservative risk profile will experience behavioral bias, especially the gambler’s fallacy and the familiarity effect, with bullish and bearish markets. Investors with a conservative risk profile will partially experience the halo effect in bullish markets.